Chapter La Pedagogia Civile per uno sviluppo territoriale sostenibile - Iavarone, Maria Luisa (Studies on Adult Learning and Education, 2022)
Nowadays poverty can be defined as a construct that can no longer be ascribed to the material scarcity of resources but to the lack of all available relational, social and cultural resources, that are an expression of a "suffering" territory. This fragility testifies to a problem of educational sustainability that requires an exit from the emergency logic of "buffer interventions" by activating social, training and professional networks, capable of responding to the educational needs expressed by the territory. For this reason, in the epistemic framework of Civil and Digital-Civil Pedagogy, the need emerges for new professional profiles capable of being "managers" of integrated territorial development, educators-planners of territorial educational services with a view to social sustainability and the educational human transition.